Second OrderMeasurement Model of Teaching Performance - Sutawanir Darwis; A Zanbar Soleh; Roslan Lacutonsina (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2005)
This paper uses second order measurement model to analyse teaching performance. Theinstrument comprising lecturer competency, lecturer attitude, lecturer organization, and studentmotivation. A survey of first year calculus student was used to test the relationships between theconstructs in the model. Students were ask to evaluate the teaching activities using a 15 itemsquestionaire on a five point Likert scale ranging from strongly agree to strongly disagree. In general,the survey results supported the proposed second order measurement model. The data showed thatthe latent construct were strongly correlated and significantly affected the quality teaching strategy.